Preparation method and application of rigid-flexible hybrid photopolymer

CN123003799APending Publication Date: 2026-10-30NANCHANG HANGKONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611403844.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-10
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但当前公开杂化技术仅实现无机颗粒与树脂宏观简单复配,未能在单分子层面集成刚性内核、耦合界面、柔性动态链,纳米相分散均匀度差、界面作用力弱;同时现有工艺缺少时序化光响应设计,无法分步触发刚性网络聚合、动态共价键可逆重组,不能从时间维度分开完成光栅成型与内应力补偿,最终制得的光栅依旧收缩偏高、耐候性不足,材料大面积涂布、层压加工适配性较差,难以匹配全息光波导中试量产生产线

Benefits of technology

本发明采用“核-壳-功能臂”一体化分子设计路线,以高折射率无机纳米颗粒(以ZrO2为例)为刚性内核,硅氧烷层搭建相容界面,表面接枝含动态二硫键的柔性功能臂,单分子内同步集成刚性增强单元与动态柔性单元;且通过时序双光束光固化成型(405nm干涉主曝光、532nm辅助光后处理照射的分段光照)调控网络生长时序,可分别控制光栅定型、内应力释放过程,为时序可调刚柔杂化全息光致聚合物制备提供全新设计思路。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123003799A_ABST
    Figure CN123003799A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a rigid-flexible hybrid photopolymer, relates to the field of organic-inorganic hybrid optical functional polymer and holographic optical cross technology, and discloses the following steps: synthesizing a core-shell-function arm three-level structure hybrid photosensitive monomer, specifically taking high refractive inorganic nanoparticles as a rigid inner core, constructing an intermediate coupling shell layer by using a siloxane coupling agent, and grafting an acrylate dynamic flexible function arm monomer containing a dynamic disulfide bond on the surface; and then compounding the core-shell-function arm three-level structure hybrid photosensitive monomer, a photoinitiator and a flexible polyurethane matrix to obtain a photopolymer precursor solution, adopting a double-beam segmented light control process of 'interference main exposure + auxiliary light post-treatment irradiation' to construct a rigid-flexible interpenetrating network, and finally obtaining the rigid-flexible hybrid photopolymer. The material can simultaneously realize high diffraction efficiency and ultra-low volume shrinkage, and is suitable for the preparation of AR holographic optical waveguide devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of organic-inorganic hybrid photofunctional polymers and holographic optics, and in particular to a method for preparing a rigid-flexible hybrid photopolymer and its application. Background Technology

[0002] Photopolymers, with their rapid photocuring, high-precision micro / nano molding, and holographic recording capabilities, have become the sole core medium for holographic volumetric gratings. Currently, the augmented reality (AR) industry is expanding rapidly, and the combination of micro-LEDs and holographic waveguides is recognized by the industry as the optimal technology for near-eye displays. Existing holographic materials suffer from drawbacks such as the inability to synergistically balance diffraction efficiency and volume shrinkage, becoming a key bottleneck in AR hardware fabrication. Developing novel photopolymers that combine multiple advantages is an urgent research challenge for the industry.

[0003] Holographic devices present dual, conflicting requirements for photopolymers: during the interference exposure recording grating stage, the material needs a high-rigidity network to lock periodic fringes, ensuring high refractive index modulation and diffraction efficiency; during lens cutting, lamination encapsulation, and high / low temperature aging, the material needs excellent toughness to release internal stress and suppress deformation cracking. Neither purely rigid nor purely flexible photopolymers can simultaneously meet these requirements. Rigid photopolymers use high-functionality acrylate monomers with high crosslinking density, resulting in well-formed gratings and excellent optical performance. However, the tightly packed molecular chains during polymerization generate significant internal stress, causing substantial volume shrinkage, leading to grating period shifts and imaging distortion. Simultaneously, the material's brittleness makes it highly susceptible to cracking during subsequent processing and aging, drastically reducing device yield and lifespan. Flexible photopolymers introduce long fatty acid chains, mitigating polymerization shrinkage and improving bending resistance. However, insufficient crosslinking strength leads to microscopic collapse of holographic fringes, directly reducing diffraction efficiency and angular selectivity, making it difficult to achieve high-definition virtual-real fusion displays. The two systems are inherently incompatible, failing to meet mass production demands.

[0004] To reconcile the contradiction between rigidity and flexibility, the industry generally adopts three modification schemes: physical blending of soft and hard monomers, simple doping of inorganic nanoparticles, and single crosslinking density control. However, all of these have significant technical drawbacks. Simple blending of soft and hard organic segments easily leads to phase separation, generating numerous light scattering defects within the film, resulting in a significant decrease in transmittance and imaging uniformity. Adjusting the functionality of a single monomer only allows for minor fine-tuning of material properties, with a narrow optimization range, failing to overcome the inherent contradiction between diffraction efficiency and shrinkage. While physical doping with high-refractive-index nanofillers such as SiO2 can slightly improve rigidity and reduce shrinkage, the nanoparticles rely solely on intermolecular forces for dispersion, making them prone to aggregation and sedimentation. The weak interface between the inorganic phase and the organic matrix leads to interface debonding and stress concentration over long-term use, impairing optical performance and shortening device lifespan. More importantly, the molecular network of these modified systems is permanently fixed after curing, making them static materials that cannot be time-divided to handle both "grating shaping" and "stress release" conditions. This is the core reason why the overall performance of existing materials is difficult to improve.

[0005] Organic-inorganic rigid-flexible hybridization is a mainstream research direction for solving performance trade-offs. Theoretically, by constructing island structures where rigid inorganic microregions and flexible organic networks coexist, optical and mechanical properties can be optimized simultaneously. However, current publicly available hybridization technologies only achieve simple macroscopic compounding of inorganic particles and resins, failing to integrate a rigid core, coupling interface, and flexible dynamic chains at the single-molecule level. This results in poor uniformity of nanophase dispersion and weak interfacial forces. Furthermore, existing processes lack time-sequential photoresponse design, making it impossible to trigger rigid network polymerization and reversible recombination of dynamic covalent bonds stepwise. It also fails to separate grating formation and internal stress compensation over time, ultimately resulting in gratings with high shrinkage and insufficient weather resistance. The materials also exhibit poor adaptability for large-area coating and lamination processes, making them unsuitable for pilot-scale production lines of holographic waveguides. Therefore, developing new organic-inorganic rigid-flexible hybridization routes to prepare photopolymers that can simultaneously achieve high diffraction efficiency and ultra-low volume shrinkage is essential. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing a rigid-flexible hybrid photopolymer and its application, so as to solve the problems existing in the prior art.

[0007] To achieve the above objectives, the present invention provides the following solution: One of the technical solutions of the present invention: a method for preparing a rigid-flexible hybrid photopolymer, comprising the following steps: High-refractive-index inorganic nanoparticles were surface modified using siloxane coupling agents containing double bonds to obtain surface double-bond modified rigid nanonuclei (i.e. modified rigid nanonuclei with polymerizable double bonds on the surface). A dynamic flexible functional arm precursor (specifically, an acrylate dynamic flexible functional arm monomer containing dynamic disulfide bonds) is prepared by polymerization reaction using diols containing disulfide bonds and acrylic anhydrides as raw materials. The surface double bond modified rigid nanonucleus, the dynamic flexible functional arm precursor and solvent are mixed and grafted to obtain a core-shell-functional arm tertiary hybrid photosensitive monomer (referred to as HHPM hybrid photosensitive monomer). The core-shell-functional arm tertiary hybrid photosensitive monomer, polyurethane matrix and photoinitiator are mixed to obtain a photopolymer precursor liquid; The photopolymer precursor liquid was coated onto the substrate surface and dried to obtain a photosensitive film. The photosensitive film is subjected to time-series dual-beam photocuring to obtain the rigid-flexible hybrid photopolymer.

[0008] This invention first synthesizes a core-shell-functional arm ternary hybrid photosensitive monomer, specifically using high-refractive-index inorganic nanoparticles as the rigid core, a siloxane coupling agent to construct the intermediate coupling shell, and acrylate dynamic flexible functional arm monomers containing dynamic disulfide bonds grafted onto the surface. Then, the core-shell-functional arm ternary hybrid photosensitive monomer, photoinitiator, and flexible polyurethane matrix are compounded to obtain a photopolymer precursor solution. A rigid-flexible interpenetrating network is constructed using a dual-beam segmented optical control process of "interference main exposure + auxiliary light post-processing irradiation," ultimately yielding a rigid-flexible hybrid photopolymer. This material can simultaneously achieve high diffraction efficiency and ultra-low volume shrinkage, making it suitable for the fabrication of devices such as AR holographic waveguides.

[0009] Furthermore, the high-refractive-index inorganic nanoparticles include ZrO2, SiO2, or HfO2 nanoparticles; the double-bonded siloxane coupling agent includes 3-acryloyloxypropyltrimethoxysilane or vinyltrimethoxysilane; and the diol containing disulfide bonds includes 2,2'-dithiodiethanol or bis(4-hydroxyphenyl)disulfide.

[0010] Further, the surface modification step includes: dispersing the high refractive index inorganic nanoparticles in a solvent, then adding the siloxane coupling agent containing double bonds, and refluxing at 65~75℃ for 4~6h; the mass ratio of the high refractive index inorganic nanoparticles to the siloxane coupling agent containing double bonds is 1:0.3~0.5.

[0011] Furthermore, the solvent used in the surface modification process includes anhydrous ethanol.

[0012] Furthermore, the ratio of the high-refractive-index inorganic nanoparticles to the solvent is 1g:80~120mL.

[0013] Furthermore, after dispersing the high-refractive-index inorganic nanoparticles in a solvent, the process further includes an ultrasonic dispersion step of 30-50 minutes.

[0014] Furthermore, after the reflux reaction is completed, the process includes centrifugation, washing, and drying; the washing uses anhydrous ethanol as the washing agent, and the drying temperature is 60~70℃.

[0015] Furthermore, the preparation steps of the dynamic flexible functional arm precursor include: mixing the diol containing disulfide bonds, the acrylic anhydride, the acid-binding agent and the solvent, and polymerizing them at 0~4℃ for 2~5h to obtain the dynamic flexible functional arm precursor; the molar ratio of the diol containing disulfide bonds and the acrylic anhydride is 1:2.0~2.2.

[0016] Furthermore, the acid-binding agent used in the polymerization reaction includes triethylamine, and the solvent includes dichloromethane.

[0017] Furthermore, the molar ratio of the diol containing disulfide bonds to the acid-binding agent is 1:1.

[0018] Furthermore, the ratio of the diol containing disulfide bonds to the solvent is 1 mol: 40~60 mL.

[0019] Furthermore, after the polymerization reaction is completed, the process also includes water washing and rotary evaporation steps.

[0020] Furthermore, the mass ratio of the surface double bond modified rigid nanonucleus to the dynamic flexible functional arm precursor is 1:0.8~1.2; the grafting reaction temperature is 55~65℃, and the time is 8~12h.

[0021] Furthermore, the photoinitiator includes camphorquinone and 4-dimethylaminobenzoic acid; the mass ratio of the core-shell-functional arm tertiary hybrid photosensitive monomer, the polyurethane matrix, and the photoinitiator is 70~85:10~25:1~3.

[0022] Furthermore, the mass ratio of camphorquinone to 4-dimethylaminobenzoic acid is 1:1~3.

[0023] Furthermore, the solvent used in the grafting reaction includes tetrahydrofuran.

[0024] Furthermore, the ratio of the surface double bond modified rigid nanonucleus to the solvent is 1 mol: 40~60 mL.

[0025] Furthermore, after the grafting reaction is completed, the process includes filtration, washing, and drying steps; the washing uses anhydrous ethanol as the detergent, and the drying temperature is 60~70℃.

[0026] Furthermore, the grafting reaction is carried out under nitrogen protection and light-protected conditions.

[0027] Furthermore, the process of mixing the core-shell-functional arm three-level hybrid photosensitive monomer, polyurethane matrix and photoinitiator is carried out under light-protected conditions, and after mixing, a step of static degassing is also included.

[0028] Furthermore, the substrate includes an optical glass substrate.

[0029] Furthermore, the coating method includes slot coating.

[0030] Furthermore, the slit coating rate is 0.8~1.5 m / min.

[0031] Furthermore, the drying temperature is 50°C and the time is 15~30 minutes.

[0032] Furthermore, the thickness of the photosensitive film is 3~20μm.

[0033] Furthermore, the time-series dual-beam photopolymerization molding includes: first using a 405nm laser for interference main exposure, and then using 532nm auxiliary light for post-processing irradiation.

[0034] Furthermore, the power of the 405nm laser is 80~120mW, and the duration of the main interference exposure is 5~15s. The purpose of the main interference exposure is to generate periodic fringe patterns using two-beam interference.

[0035] Furthermore, the power of the 532nm auxiliary light is 30~50mW, and the duration of the post-processing irradiation is 20~40s.

[0036] Furthermore, after post-treatment irradiation with 532nm auxiliary light, the process also includes a step of curing at room temperature for 20~28 hours.

[0037] The second technical solution of the present invention: a rigid-flexible hybrid photopolymer prepared by the above-described method.

[0038] Furthermore, the rigid-flexible hybrid photopolymer is specifically a rigid-flexible hybrid photopolymer holographic film.

[0039] The third technical solution of the present invention: the application of the above-mentioned rigid-flexible hybrid photopolymer in the fabrication of AR holographic waveguide devices or vehicle-mounted augmented reality head-up displays.

[0040] This invention designs an integrated hybrid monomer consisting of a "high-refractive-index inorganic core-siloxane interface shell-dynamic covalent flexible functional arm" (referred to as "core-shell-functional arm"), achieving uniform dispersion of nanounits through chemical bonds. A dual-beam process, employing "interference master exposure shaping rigid grating and auxiliary light post-processing irradiation activation dynamic network decompression," simultaneously achieves high diffraction efficiency and ultra-low shrinkage. The preparation method of this invention allows precise control of the grafting reaction on the nanoparticle surface without compromising particle dispersion. This method also simultaneously addresses the pain points of photopolymers, such as filler agglomeration, weak interfaces, and curing shrinkage, providing a new generation of high-performance photopolymers for AR holographic waveguides.

[0041] The present invention discloses the following technical effects: This invention adopts an integrated molecular design route of "core-shell-functional arm", using high-refractive-index inorganic nanoparticles (taking ZrO2 as an example) as a rigid core, a siloxane layer to build a compatible interface, and flexible functional arms with dynamic disulfide bonds grafted on the surface. Rigid reinforcement units and dynamic flexible units are simultaneously integrated within a single molecule. Furthermore, the network growth sequence is controlled by time-sequential dual-beam photopolymerization (segmented illumination with 405nm interference main exposure and 532nm auxiliary light post-processing irradiation), which can separately control the grating shaping and internal stress release process, providing a new design concept for the preparation of time-tunable rigid-flexible hybrid holographic photopolymers.

[0042] The rigid-flexible hybrid photopolymer prepared by this invention integrates the dual advantages of an inorganic rigid phase and a dynamic flexible network: the siloxane covalent grafting structure completely solves the defects of inorganic nanoparticle aggregation and matrix interface debonding, significantly improving the material transmittance, while improving the compatibility of fillers with organic matrices and ensuring the adaptability of thin film processing, lamination, cutting and other processes; in the interference main exposure stage, the rigid inorganic micro-regions rapidly construct a highly regular grating, obtaining a high refractive index modulation and diffraction efficiency; the auxiliary light post-processing irradiation activates the reversible recombination of dynamic disulfide bonds, effectively releasing the internal stress of polymerization, suppressing volume shrinkage, and taking into account both high imaging accuracy and low deformation defects.

[0043] The rigid inorganic nanoparticles within the system can restrict molecular chain stacking and inhibit curing shrinkage, while the dynamic flexible segments play a buffering and toughening role. The two form a rigid-flexible interpenetrating island structure, which makes the material less prone to cracking under bending and thermal cycling conditions, significantly improving its environmental durability. The rigid framework and the dynamic flexible network work synergistically to break through the technical barrier that traditional materials cannot simultaneously achieve diffraction efficiency and low shrinkage, making it perfectly suited for demanding optical applications such as Micro-LED holographic AR waveguides and automotive AR-HUDs (augmented reality head-up displays).

[0044] This invention first controllably synthesizes a core-shell-functional arm three-level hybrid photosensitive monomer, then formulates a photopolymer precursor liquid (which is a holographic photosensitive precursor liquid) after compounding, and combines it with a dual-beam segmented light control process of "interference main exposure + auxiliary light post-processing irradiation". The process is simple, controllable and highly repeatable. The rigid-flexible hybrid photopolymer prepared by this invention can be applied to AR holographic waveguide devices, providing a complete and feasible technical solution for the development of core optical functional materials in the upstream of AR. Attached Figure Description

[0045] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0046] Figure 1 This is a schematic diagram of the core-shell-functional arm three-level hybrid photosensitive monomer (referred to as HHPM hybrid photosensitive monomer) in this invention.

[0047] Figure 2 Scanning electron microscope image of the rigid-flexible hybrid photopolymer holographic film PU / PMMA-1 prepared in Example 1.

[0048] Figure 3 This is a physical image of the holographic grating formed by irradiating the rigid-flexible hybrid photopolymer holographic film PU / PMMA-1 prepared in Example 1 with an ultraviolet light source.

[0049] Figure 4 The transmittance test results are for the photopolymer holographic films prepared in Examples 1-4 and Comparative Example 1.

[0050] Figure 5 The diffraction efficiency test results are for the photopolymer holographic films prepared in Examples 1-4 and Comparative Example 1.

[0051] Figure 6 The volume shrinkage rate of the monomers in Examples 1-4 and Comparative Example 1 during the holographic photopolymerization process is given.

[0052] Figure 7 The volume shrinkage rate of the monomers in Comparative Examples 2-7 during the holographic photopolymerization process is shown. Detailed Implementation

[0053] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0054] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0055] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0056] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0057] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0058] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0059] The structural schematic diagram of the core-shell-functional arm three-level hybrid photosensitive monomer (referred to as HHPM hybrid photosensitive monomer) in this invention is shown below. Figure 1 As shown, it uses high-refractive-index inorganic nanoparticles (taking ZrO2 as an example) as a rigid core, forms a transition shell with the help of siloxane coupling agents, and extends outwards with flexible organic chain segments with dynamic disulfide bonds as "arms". The rigid inorganic nanoparticles can increase the refractive index and inhibit the close packing of polymer chains, while the flexible organic chains act as stress buffers. During the main interference exposure, the terminal double bonds undergo photopolymerization, inducing the periodic distribution of components, and finally forming a holographic grating, realizing the synergistic optimization of the inorganic rigid phase and the organic flexible phase.

[0060] Unless otherwise specified, the room temperature mentioned in the following embodiments, comparative examples and test examples of this invention refers to 20-30°C.

[0061] Unless otherwise specified, all raw materials used in the following embodiments, comparative examples and test examples of this invention are commercially available products. Among them, the ZrO2 nanoparticles are monodisperse ZrO2 powders with a particle size of 10 nm, which are high refractive index inorganic nanoparticles; the number average molecular weight of polyurethane is 2000.

[0062] Example 1 A method for preparing a rigid-flexible hybrid photopolymer, comprising the following steps: Step 1: Surface modification of high-refractive-index inorganic nanoparticles (i.e., high-refractive-index rigid nanonuclei) 1 g of ZrO2 nanoparticles were dispersed in 100 mL of anhydrous ethanol and ultrasonically dispersed for 40 min. Then, 0.4 g of 3-acryloyloxypropyltrimethoxysilane was added, and the mixture was stirred and heated to 70 °C and refluxed for 5 h. After the reaction was completed, the mixture was centrifuged, the precipitate was washed several times with anhydrous ethanol, and dried under vacuum at 65 °C to obtain ZrO2 rigid nanonuclei with surface double bonds modified.

[0063] Step 2, Synthesize the precursor of the dynamic flexible functional arm 1 mol of 2,2'-dithiodiethanol and 2.1 mol of acrylic anhydride were dissolved in 50 mL of dichloromethane. Triethylamine, in an equimolar amount as an acid-binding agent, was added, and the mixture was stirred in an ice-water bath (0 °C) for 3 h. After the reaction was completed, the salt impurities were removed by washing with water, and the solvent was removed by rotary evaporation to obtain an acrylate containing dynamic disulfide bonds, which is the precursor of the dynamic flexible functional arm. Its structural formula is as follows: .

[0064] Step 3: Prepare a core-shell-functional arm ternary hybrid photosensitive monomer (referred to as HHPM hybrid photosensitive monomer). 1g of the surface double bond modified ZrO2 rigid nanonucleus prepared in step 1 was dispersed in 50mL of anhydrous tetrahydrofuran, and 1g of the dynamic flexible functional arm precursor prepared in step 2 was added. The grafting reaction was carried out at 60℃ for 10h under nitrogen protection and in the dark. After the reaction was completed, the solid was collected by filtration, washed repeatedly with anhydrous ethanol, and dried under vacuum at 70℃ to obtain the HHPM hybrid photosensitive monomer.

[0065] Step 4: Prepare the photopolymer precursor solution (i.e., the holographic photosensitive precursor solution). By mass, 80 parts of the HHPM hybrid photosensitive monomer prepared in step 3, 18 parts of polyurethane matrix, and 2 parts of camphorquinone / 4-dimethylaminobenzoic acid complex photoinitiator (the mass ratio of camphorquinone to 4-dimethylaminobenzoic acid is 1:2) were stirred and mixed evenly at room temperature in the dark, and allowed to stand for 20 minutes to remove bubbles, resulting in a uniform and transparent photopolymer precursor solution.

[0066] Step 5, thin film coating preforming A slit coater was used to uniformly coat the photopolymer precursor liquid onto the surface of an optical glass substrate at a coating speed of 1 m / min. The substrate was then dried in a 50°C oven for 20 min to obtain a uniform photosensitive film with a thickness of 5 μm.

[0067] Step 6, Time-sequential dual-beam photopolymerization molding First, a dual-beam interference optical path was constructed using a 100mW, 405nm continuous semiconductor laser. The angle between the two coherent laser beams was adjusted to 28°, and a 10s main interference exposure was performed on the uniform photosensitive film. Spatial selective holographic photopolymerization was achieved with the help of the periodic interference optical field to construct a high-rigidity regular diffraction framework (i.e., grating framework). Then, a 40mW, 532nm continuous solid-state laser was used. After beam expansion and homogenization, the output uniform floodlight was used as auxiliary light for post-processing irradiation for 30s to activate the dynamic disulfide bonds to undergo reversible recombination and release the polymerization internal stress in situ. Then, the film was allowed to stand at room temperature for 24 hours to cure, resulting in a rigid-flexible hybrid photopolymer holographic film, denoted as PU / PMMA-1, which is the rigid-flexible hybrid photopolymer mentioned above.

[0068] Example 2 The only difference between this embodiment and Embodiment 1 is that in step 5, the thickness of the obtained uniform photosensitive film is controlled to be 10 μm, and the rigid-flexible hybrid photopolymer holographic film obtained in this embodiment is denoted as PU / PMMA-2.

[0069] Example 3 The only difference between this embodiment and Embodiment 1 is that in step 5, the thickness of the obtained uniform photosensitive film is controlled to be 15 μm, and the rigid-flexible hybrid photopolymer holographic film obtained in this embodiment is denoted as PU / PMMA-3.

[0070] Example 4 The only difference between this embodiment and Embodiment 1 is that in step 5, the thickness of the obtained uniform photosensitive film is controlled to be 20 μm, and the rigid-flexible hybrid photopolymer holographic film obtained in this embodiment is denoted as PU / PMMA-4.

[0071] Comparative Example 1 Step 1, Prepare photopolymer precursor solution By weight, 80 parts of commercially available acrylate monomer (o-phenylphenoxyethyl acrylate), 18 parts of polyurethane matrix, and 2 parts of camphorquinone / 4-dimethylaminobenzoic acid compound initiator were stirred and mixed evenly at room temperature in the dark, and allowed to stand for 20 minutes to remove bubbles, resulting in a uniform and transparent photopolymer precursor liquid.

[0072] Step 2, thin film coating preforming A slit coater was used to uniformly coat the photopolymer precursor liquid onto the surface of an optical glass substrate at a coating speed of 1 m / min. The substrate was then dried in a 50°C oven for 20 min to obtain a uniform photosensitive film with a thickness of 5 μm.

[0073] Step 3, Time-sequential dual-beam photopolymerization molding First, a dual-beam interference optical path was constructed using a 100mW, 405nm continuous semiconductor laser. The angle between the two coherent laser beams was adjusted to 28°, and a 10s main interference exposure was performed on the uniform photosensitive film. Spatial selective holographic photopolymerization was achieved by using the periodic interference optical field to construct a rigid grating framework. Then, a 40mW, 532nm continuous solid-state laser was used. After beam expansion and homogenization, the output uniform floodlight was used as auxiliary light for post-processing irradiation for 30s. After curing at room temperature for 24h, a photopolymer holographic film was obtained, denoted as PU / PMMA-0.

[0074] Comparative Example 2 The only difference between this comparative example and Example 1 is that step 1 is omitted, and unmodified pure ZrO2 nanoparticles are used directly in the subsequent synthesis. The rigid-flexible hybrid photopolymer holographic film obtained in this comparative example is denoted as PU / PMMA-1-0.

[0075] Comparative Example 3 The only difference between this comparative example and Example 2 is that step 1 is omitted, and unmodified pure ZrO2 nanoparticles are used directly in the subsequent synthesis. The rigid-flexible hybrid photopolymer holographic film obtained in this comparative example is denoted as PU / PMMA-2-0.

[0076] Comparative Example 4 The only difference between this comparative example and Example 3 is that step 1 is omitted, and unmodified pure ZrO2 nanoparticles are used directly in the subsequent synthesis. The rigid-flexible hybrid photopolymer holographic film obtained in this comparative example is denoted as PU / PMMA-3-0.

[0077] Comparative Example 5 The only difference between this comparative example and Example 4 is that step 1 is omitted, and unmodified pure ZrO2 nanoparticles are used directly in the subsequent synthesis. The rigid-flexible hybrid photopolymer holographic film obtained in this comparative example is denoted as PU / PMMA-4-0.

[0078] Comparative Example 6 The only difference between this comparative example and Example 1 is that step 2 is omitted, and unmodified methyl acrylate is used directly in the subsequent synthesis (i.e., in step 3, the dynamic flexible functional arm precursor is replaced by methyl acrylate in equal mass). The rigid-flexible hybrid photopolymer holographic film obtained in this comparative example is denoted as PU / PMMA-1-1.

[0079] Comparative Example 7 The only difference between this comparative example and Example 1 is that in step 6, only 100mW, 405nm dual-beam interference is used to complete the 10s main exposure, and the 532nm auxiliary light post-processing irradiation step is omitted. Subsequently, the film is cured at room temperature for 24 hours. The other raw material ratios, film preparation, exposure angle and other conditions are completely consistent with those of Example 1. The rigid-flexible hybrid photopolymer holographic film obtained in this comparative example is denoted as PU / PMMA-1-2.

[0080] Test Example 1 Characterization data: Taking the rigid-flexible hybrid photopolymer holographic film PU / PMMA-1 prepared in Example 1 as an example, the morphology of the three-dimensional network structure of the holographic bulk grating was observed using a scanning electron microscope, and the results are as follows: Figure 2 As shown. During the dual-beam interference main exposure, the bright region initiates rapid polymerization of monomers, and the high-refractive-index rigid ZrO2 nanonuclei in the HHPM hybrid photosensitive monomer are fixed there, forming a high-refractive-index dense cross-linked region; the dark region does not undergo photopolymerization, leaving a large number of low-refractive-index flexible monomers. Driven by the concentration difference, the flexible components in the dark region diffuse into the bright region, causing a significant difference in refractive index between the bright and dark regions. The film has a periodic alternation of high and low refractive indices, initially forming a phase-type holographic grating. The width of the bright region (high-refractive-index polymer diffraction framework) in the holographic grating is 440±20nm, and the width of the dark region (low-refractive-index flexible matrix gap region) is 370±20nm. The physical image of the holographic grating formed after irradiating the rigid-flexible hybrid photopolymer holographic film PU / PMMA-1 prepared in Example 1 with a 365nm, 10mW / cm² ultraviolet light source for 2 min is shown in the figure. Figure 3 As shown.

[0081] Test Example 2 Optical performance testing: The transmittance of the photopolymer holographic film in the 400-750 nm wavelength range was measured using a UV-Vis spectrophotometer. The minimum transmittance T of the reflection peak was obtained from the transmittance curve. min With maximum light transmittance T max Then, the diffraction efficiency (η) of the holographic grating is calculated according to formula (1).

[0082] η=(T max -T min ) / T max ×100% (1) The transmittance test results of the photopolymer holographic films prepared in Examples 1-4 and Comparative Example 1 are as follows: Figure 4 As shown, the calculated diffraction efficiency results are as follows: Figure 5As shown in Table 1, the diffraction efficiency results of the photopolymer holographic films prepared in Examples 1-4 and Comparative Examples 1-7 are shown in Table 1. The results show that as the thickness of the photopolymer holographic film increases, the film transmittance gradually decreases, while the diffraction efficiency continuously increases. When the film thickness increases from 5 μm to 20 μm, the diffraction efficiency increases from 89.9% to 95.5%. From the perspective of grating optical mechanism, the diffraction effect of the bulk grating accumulates along the film thickness direction. The thicker the film, the more layers of alternating high and low refractive indices there are, resulting in stronger coupling between light and the grating structure, and an increased proportion of light energy converted into diffracted light, thus continuously increasing the diffraction efficiency. However, increasing the film thickness also increases the light scattering loss of the organic matrix and inorganic fillers, lengthens the absorption path, and ultimately causes a continuous decrease in the overall transmittance of the film. Comparing Example 1 with Comparative Example 1 without ZrO2 rigid nanoparticles, the diffraction efficiency of the pure organic photopolymer without ZrO2 is only 82.3%, showing a significant performance difference. The reason lies in the high refractive index of ZrO2. When covalently grafted into the HHPM hybrid photosensitive monomer and enriched in the bright exposure area, it significantly widens the refractive index difference between the bright and dark regions of the grating, thus improving the refractive index modulation. Simultaneously, the rigid ZrO2 framework stabilizes the periodic microstructure of the grating, suppressing fringe distortion caused by polymerization shrinkage and ensuring the integrity and regularity of the periodic morphology formed by light field interference. In the pure organic system without ZrO2 filler, the refractive index difference between the bright and dark phases is small, and the polymerization process easily generates internal stress, leading to grating deformation. Ultimately, the diffraction efficiency is far lower than that of the rigid-flexible hybrid photopolymer film in Example 1. Comparing Example 1 with Comparative Example 6, which directly uses unmodified acrylate, and Comparative Example 7, which does not undergo sequential two-beam photopolymerization, the diffraction efficiencies of Comparative Examples 6-7 show little change, but are all slightly lower than those of Example 1.

[0083] Table 1 Test Example 3 Volume shrinkage rate test: In reflective holographic gratings, the volume shrinkage of monomers during holographic light aggregation reduces the grating spacing of the resulting holographic grating. This invention derives the volume shrinkage rate of the holographic grating by calculating the change in grating spacing. The relationship between the grating spacing of the reflective holographic grating and the recording wavelength and incident angle is shown in formula (2).

[0084] (2) in, The grating spacing is Let n be the recording wavelength, n be the average refractive index of the recording material, and θ be the angle between the two coherent laser beams. When the laser beam is perpendicular to the recording medium, θ = 180°. (3) Reconstructed wavelength of reflective grating Satisfying formula (4): (4) After photopolymerization occurs, the volume shrinkage causes... Reduced, leading to Therefore, the volume shrinkage rate S of the reflective grating v Satisfying formula (5): (5) The test results of the volume shrinkage rate of the monomers in Examples 1-4 and Comparative Examples 1-7 during the holographic photopolymerization process are as follows: Figures 6-7 As shown. Among them, Figure 6 The volume shrinkage rates of Examples 1-4 and Comparative Example 1 are given. Figure 7 The volume shrinkage rate is for comparative examples 2-7.

[0085] The results show that the volume shrinkage rate of the holographic grating gradually increases with the increase of the photopolymer holographic film thickness. When the film thickness increases from 5 μm to 20 μm, the volume shrinkage rate increases from 0.43% to 0.63%. From the polymerization mechanism analysis, the photopolymer undergoes free radical cross-linking reaction only in the bright interference region, where free monomers are transformed into a dense polymer network. The increased molecular packing density naturally leads to inherent polymerization shrinkage. The larger the film thickness, the greater the total amount of monomers participating in the curing reaction along the incident light direction, and the more significant the cumulative effect of size shrinkage caused by cross-linking becomes. Therefore, the overall volume shrinkage rate continues to increase with the increase of film thickness.

[0086] Comparing Example 1 with Comparative Example 1 (without ZrO2 rigid nanoparticles), the volume shrinkage rate of the pure organic photopolymer holographic grating without ZrO2 is as high as 3.51%, a significant difference. The pure organic system relies solely on the crosslinking of flexible and rigid organic segments, lacking an inorganic rigid framework for support. The internal stress generated by photopolymerization cannot be effectively offset, and the tightly packed molecular chains are prone to significant shrinkage, leading to periodic shifts in the grating fringes and directly disrupting Bragg diffraction conditions. In contrast, the HHPM hybrid photosensitive monomer of this invention has a covalently bonded high-hardness ZrO2 inorganic core, which acts as a physical support framework to constrain molecular chain shrinkage, limiting dimensional deformation caused by crosslinking at the microscopic level and significantly reducing the overall shrinkage level.

[0087] Comparing Examples 1-4 with Comparative Examples 2-5, the volume shrinkage rate of the holographic grating synthesized directly using unmodified pure ZrO2 nanoparticles was significantly increased, reaching approximately 3%. The ZrO2 nanoparticles, without modification by the siloxane coupling agent, were merely physically dispersed within the resin matrix; there were no chemical bonds between the particles and the organic interface. During photopolymerization, when the organic network shrinks, the inorganic particles cannot be synchronously stressed with the polymer chains, leading to easy interface debonding and an inability to provide stable support and inhibit shrinkage. Ultimately, the grating shrinkage rate was much higher than in the examples using covalently grafted modified ZrO2.

[0088] Compared with Comparative Example 6, the volume shrinkage rate of the holographic grating synthesized directly using unmodified methyl acrylate without dynamic disulfide bonds significantly increased, reaching 3.55%. This is because during the photopolymerization and crosslinking process of acrylate monomers containing dynamic disulfide bonds to form a resin network, the disulfide bonds can effectively mitigate the internal stress generated by the photopolymerization reaction through reversible breakage-recombination dynamic exchange. However, the crosslinked network formed by methyl acrylate monomers without dynamic disulfide bonds does not have this stress buffering ability and is unable to offset the volume shrinkage effect brought about by photopolymerization, ultimately resulting in a higher volume shrinkage rate.

[0089] Compared with Comparative Example 7, the volume shrinkage rate of the holographic grating, achieved by using only 100mW, 405nm dual-beam interference for 10s main exposure, significantly increased to 4.11%. Even after omitting the 532nm auxiliary light post-processing irradiation, although the interference main exposure could still form a periodic grating structure, the dynamic disulfide bonds were not effectively activated, preventing reversible bond recombination to dissipate the internal stress rapidly accumulated during photopolymerization. A large amount of residual internal stress was trapped within the grating crosslinking network, resulting in even greater volume shrinkage of the film.

[0090] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for preparing a rigid-flexible hybrid photopolymer, characterized in that, Includes the following steps: Surface modification of high-refractive-index inorganic nanoparticles was carried out using a siloxane coupling agent containing double bonds to obtain rigid nanonuclei with modified surface double bonds. A precursor for a dynamic flexible functional arm was prepared by polymerization reaction using diols containing disulfide bonds and acrylic anhydrides as raw materials. The surface double bond modified rigid nanonucleus, the dynamic flexible functional arm precursor and solvent are mixed and grafted to obtain a core-shell-functional arm tertiary hybrid photosensitive monomer. The core-shell-functional arm tertiary hybrid photosensitive monomer, polyurethane matrix and photoinitiator are mixed to obtain a photopolymer precursor liquid; The photopolymer precursor liquid was coated onto the substrate surface and dried to obtain a photosensitive film. The photosensitive film is subjected to time-series dual-beam photocuring to obtain the rigid-flexible hybrid photopolymer.

2. The method for preparing the rigid-flexible hybrid photopolymer as described in claim 1, characterized in that, The high-refractive-index inorganic nanoparticles include ZrO2, SiO2, or HfO2 nanoparticles; the siloxane coupling agent containing double bonds includes 3-acryloyloxypropyltrimethoxysilane or vinyltrimethoxysilane; the diol containing disulfide bonds includes 2,2'-dithiodiethanol or bis(4-hydroxyphenyl)disulfide.

3. The method for preparing the rigid-flexible hybrid photopolymer as described in claim 1, characterized in that, The surface modification step includes: dispersing the high refractive index inorganic nanoparticles in a solvent, then adding the siloxane coupling agent containing double bonds, and refluxing at 65~75℃ for 4~6h; the mass ratio of the high refractive index inorganic nanoparticles to the siloxane coupling agent containing double bonds is 1:0.3~0.

5.

4. The method for preparing the rigid-flexible hybrid photopolymer as described in claim 1, characterized in that, The preparation steps of the dynamic flexible functional arm precursor include: mixing the diol containing disulfide bonds, the acrylic anhydride, the acid-binding agent and the solvent, and polymerizing them at 0~4℃ for 2~5h to obtain the dynamic flexible functional arm precursor; the molar ratio of the diol containing disulfide bonds and the acrylic anhydride is 1:2.0~2.

2.

5. The method for preparing the rigid-flexible hybrid photopolymer as described in claim 1, characterized in that, The mass ratio of the surface double bond modified rigid nanonucleus to the dynamic flexible functional arm precursor is 1:0.8~1.2; the grafting reaction temperature is 55~65℃ and the time is 8~12h.

6. The method for preparing the rigid-flexible hybrid photopolymer as described in claim 1, characterized in that, The photoinitiator includes camphorquinone and 4-dimethylaminobenzoic acid; the mass ratio of the core-shell-functional arm tertiary hybrid photosensitive monomer, the polyurethane matrix and the photoinitiator is 70~85:10~25:1~3.

7. The method for preparing the rigid-flexible hybrid photopolymer as described in claim 1, characterized in that, The thickness of the photosensitive film is 3~20μm.

8. The method for preparing the rigid-flexible hybrid photopolymer as described in claim 1, characterized in that, The time-series dual-beam photopolymerization process includes: first, using a 405nm laser for interference main exposure, and then using 532nm auxiliary light for post-processing irradiation.

9. A rigid-flexible hybrid photopolymer prepared by a method according to any one of claims 1 to 8.

10. The application of the rigid-flexible hybrid photopolymer as described in claim 9 in the fabrication of AR holographic waveguide devices or automotive augmented reality head-up displays.